IMPLEMENTING A MIKROTIK RECURSIVE FAILOVER SYSTEM TO ENSURE INTERNET NETWORK AVAILABILITY AT PT. OMEGA MEDIA GLOBAL - Achmad Ridduan,; Rachmawati Darma Astuti,; Arina Selawati, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The availability of a stable internet connection is essential for maintaining smooth business operations, especially in digital-based companies like PT. Omega Media Global. Relying solely on a single internet connection creates a major risk, as any disruption may halt the entire workflow. To address this issue, this study implements a network system using the failover recursive gateway method on Mikrotik devices. This system is designed to automatically monitor the stability of the primary internet link and seamlessly switch to a backup connection in the event of a failure, based on preconfigured priorities and connection speed. The implementation results indicate that the system successfully performs automatic failover without manual intervention, effectively reducing downtime and maintaining connection stability. The application of this method has proven to significantly improve network reliability and operational efficiency, enabling the company to continue its digital activities without interruption during internet failures.